Pengaruh Senam Nifas Terhadap Tinggi Fundus Uteri Pada Ibu Nifas Di Wilayah Kerja Puskesmas Cimanggu Kabupaten Pandeglang Banten Tahun 2022: The Effect of Postpartum Exercise on Uterine Fundal Height in Postpartum Mothers in the Work Area of the Cimanggu Health Center, Pandeglang Regency, Banten in 2022 - Widianingsih, Wacih (Dohara POAJ, 2023)
Introduction: The puerperium undergoes physiological changes, including the uterine system undergoing a process of shrinking (involution). Postpartum exercise is one of the efforts to help accelerate uterine involution. The results of a preliminary study at Cimanggu Public Health Center, Pandeglang Regency, Banten to 10 postpartum mothers, found 6 of them with TFU exceeding the middle of the center and the symphysis. The purpose of the study was to determine the effect of postpartum gymnastics on uterine fundal height in postpartum women in the work area of Cimanggu Health Center, Pandeglang Regency, Banten in 2022. Methods: The research method was a quasi-experimental design with pre-test and post-test design with control groups design, the number of samples was 64 respondents, and the sampling technique was purposive sampling. The data analysis used an Independent T-test test. Results: The results of this study of TFU before the postpartum exercise intervention in postpartum women on average = 12,094 cm and after the intervention the average = 3,375 cm, TFU before the control group on average = 11,969 cm and after the intervention the average = 6,0 cm. The results of the bivariate analysis showed that there was an effect of postpartum gymnastics on the decrease in uterine fundal height in postpartum women in the work area of Cimanggu Public Health Center, Pandeglang Regency, Banten in 2022 with a p-value of 0,000. Discussion: The conclusion of the research is that there is an effect of puerperal exercise on decreasing uterine fundal height in postpartum women. It is recommended that postpartum mothers can do postpartum exercises at home regularly every morning and evening according to the midwife's recommendations.